Arginine deiminase system and acid adaptation of oral streptococci. - Curran, T M (1995)
Streptococcus rattus FA-1 and Streptococcus sanguis NCTC 10904 underwent phenotypic acid adaptation in batch cultures toward the end of sugar-fueled growth after the culture pH had dropped to triggering values. The bacteria could be derepressed or induced for arginine deiminase independently of acid adaptation, and arginolysis afforded protection against acid killing over and above that of acid adaptation.